1993
DOI: 10.1037/0096-1523.19.6.1183
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and cognitive factors governing performance in comparative arrival-time judgments.

Abstract: Four experiments were conducted to investigate factors affecting relative arrival-time judgments in the transverse plane. Across experiments, results indicated an overreliance on relative distance information. The levels of relative velocity and distance used in the arrival-time task were proved discriminable, and performance in both relative velocity and distance judgments predicted performance in the relative arrival-time task. Despite the distance bias, an attempt to integrate relative velocity and distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 39 publications
10
87
1
Order By: Relevance
“…This finding is consistent with previous studies (e.g., Oberfeld & Hecht, 2008;Petzoldt, 2014), and can be attributed to either a size-arrival effect (DeLucia, 1991) or a distance bias (Law et al, 1993), because the slower speed condition had a larger final optical vehicle size and a closer final distance than did the faster condition. A significant interaction between TTC level and speed, F(2, 80) = 27.397,ε = 1.000, p < .001, η p 2 = .407, indicated larger differences in TTC estimates between the two speeds with increasing actual TTC (see Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is consistent with previous studies (e.g., Oberfeld & Hecht, 2008;Petzoldt, 2014), and can be attributed to either a size-arrival effect (DeLucia, 1991) or a distance bias (Law et al, 1993), because the slower speed condition had a larger final optical vehicle size and a closer final distance than did the faster condition. A significant interaction between TTC level and speed, F(2, 80) = 27.397,ε = 1.000, p < .001, η p 2 = .407, indicated larger differences in TTC estimates between the two speeds with increasing actual TTC (see Fig.…”
Section: Resultssupporting
confidence: 83%
“…We also observed a significant effect of vehicle speed on TTC estimates, indicating that estimates were shorter when vehicle speed was slower. This finding is consistent with previous studies (e.g., Oberfeld & Hecht, 2008;Petzoldt, 2014) and can be attributed to a size-arrival effect (DeLucia, 1991) or to a distance bias (Law et al, 1993). Specifically, at slower speeds, when the screen goes blank, the final optical vehicle size is larger, and the vehicle is closer in terms of final distance, than in the faster condition.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, in the AI task, this type of cognitive influences is minimized (cf. DeLucia & Novak, 1997;Law et al, 1993). Thus, the two types of tasks differ in terms of the processing involved.…”
Section: Experiments 5: Pm Taskmentioning
confidence: 99%
“…However, results also suggest that judgments about TTC are constrained by scene and threshold factors and can be based on multiple sources of information (see, e.g., DeLucia, 1991aDeLucia, , 1991bDeLucia, , 1995DeLucia & Warren, 1994;Law et al, 1993;Schiff & Detwiler, 1979;Schiff & Oldak, 1990;Tresilian, 1995). For example, results of the previously mentioned PM task indicated that observers estimated TTC inaccurately when actual TTC exceeded 2 sec, and that the inaccuracy increased as actual TTC increased; the majority ofjudgments were underestimations (Schiff & Detwiler, 1979;Schiff & Oldak, 1990).…”
mentioning
confidence: 99%